IMPLEMENTASI GREEN MARKETING PADA PRODUK URBAN FARMING UMKM LOKAL - Sekar Widyasari Putri; Tiar Anindya Putri (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The COVID-19 pandemic has impacted on various sectors of life, including the Micro, Small and Medium Enterprises sector(MSME). The PPKM policy has stopped MSME exhibitions, while most of their sales were through exhibitions.Exhibitions make their products available to many people to see and buy. MSME actors want to sell their products online, but based on surveys and discussions with community groups and owners of several MSMEs, the main problem is the lack of use of attractive product packaging so that they can compete on online selling platforms. Proper packaging can improve the marketing process to consumers, but in determining good packaging it is necessary to choose packaging that can reduce the negative impact on the environment. Efforts to reduce plastic packaging waste have become the latest trend of marketing. By paying attention to environmental issues, packaging redesign activities obtained through analysis of digital market trends that focus on green marketing are expected to be an alternative solution to overcome these problems. So, this Community Service activity is expected to contribute in terms of knowledge about Green Marketing, to improve the marketing process so that they can compete on online selling platforms, so that problems can be resolved through the use of sustainable packaging, green marketing, digital marketing trends, and empowering Wonokusumo’s MSMEs